The effect of caffeine chewing gum on muscle performance and fatigue after severe-intensity exercise: isometric vs. dynamic assessments in trained cyclists - Nascimento, Eduardo Marcel Fernandes; Borszcz, Fernando Klitzke; Ventura, Thiago Pereira; Denadai, Benedito Sérgio [UNESP]; Guglielmo, Luiz Guilherme Antonacci; de Lucas, Ricardo Dantas (Springer Nature, 2025)
This study investigated the effect of caffeinated chewing gum (GUMCAF) on muscle fatigue (isometric vs. dynamic) after severe-intensity cycling bouts. Fifteen trained male cyclists participated in four visits. Each visit involved two severe-intensity cycling bouts (Δ1 and Δ2) lasting 6 min, separated by a 5-min recovery period. Muscle fatigue was assessed by isometric maximal voluntary knee extension contraction (IMVC) with twitch interpolation technique and dynamically by 7 s all-out cycling sprints. Assessments were performed before GUMCAF (Pre-GUM) and after the cycling bouts (Post-Exercise). GUMCAF and placebo gum (GUMPLA) were administered in a randomized double-blind procedure with participants receiving each gum type (GUMCAF and GUMPLA) during two separate visits. The results showed no significant interaction between gum types and time for the isometric and dynamic measurements (p > 0.05). The percentage change in performance from Pre-GUM to Post-Exercise showed no significant difference between GUMCAF and GUMPLA for either the dynamic-derived TMAX (~ −17.8% and −15.1%, respectively; p = 0.551) or isometric IMVC (~ −12.3% and −17.7%, respectively; p = 0.091) measurements. Moderate to large correlations (r = 0.31–0.51) were found between changes in sprint maximal torque and maximal power output measurements and isometric force, for both gum conditions. GUMCAF was not effective in attenuating muscle force decline triggered by severe-intensity cycling exercises, as measured by both isometric and dynamic methods. The correlations between IMVC and cycling maximal torque and power output suggest caution when interpreting isometric force as a direct measure of fatigue during dynamic cycling exercises.
Keywords: Caffeine; Fatigue; Isometric maximal voluntary contraction; Maximal power output; Neuromuscular functions; Sprinting